2018
DOI: 10.21037/tp.2018.09.10
|View full text |Cite
|
Sign up to set email alerts
|

Making care better in the pediatric intensive care unit

Abstract: The relatively young field of pediatric critical care has seen a shift from an approach with little consideration for the complications and adverse effects resulting from the procedures and medications to a more cautious approach with careful concern for the associated risks. Many senior pediatric intensivists recall a time when nearly every patient had a central venous line and arterial line; and hospital acquired infections, pressure injuries, unplanned extubations, and venous thromboemboli were expected cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The most vulnerable patients with life-threatening conditions who require comprehensive care and constant monitoring are admitted to hospital intensive care units (ICUs). Depending on the patient’s age and medical condition, the patient could be admitted to specialized ICUs such as a neonatal intensive care unit (NICU), 1 a pediatric intensive care unit, 2 or a neurointensive care unit. 3 The mortality in an adult ICU can range from 10% to 29%, depending on age, illness severity, and morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…The most vulnerable patients with life-threatening conditions who require comprehensive care and constant monitoring are admitted to hospital intensive care units (ICUs). Depending on the patient’s age and medical condition, the patient could be admitted to specialized ICUs such as a neonatal intensive care unit (NICU), 1 a pediatric intensive care unit, 2 or a neurointensive care unit. 3 The mortality in an adult ICU can range from 10% to 29%, depending on age, illness severity, and morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…As for frequency, studies reported safety outcomes as the second main domain, indicating, hence, that health-care-associated infections and critical incidents are a tangible concern in the PICU setting. Healthcare professionals have moved from a culture of acceptance, in which complications and adverse effects were expected, to a point where these harms are no longer tolerable and are preventable in many cases [30], both for the individual and for the collective costs [31]. Several studies have also shown that some negative outcomes (e.g., nosocomial infections) lead to substantial additional LOS and morbidity [5], thus strengthening the side effects of hospitalisation that also merit consideration by nurses.…”
Section: Nsos and Metrics Documented To Date In Picusmentioning
confidence: 99%
“…This high incidence is due to the clinical complexity of the patients, the pressure associated with urgent situations, the length of stay, the invasive nature of the procedures, the therapeutic intensity and the use of complex equipment (1,45). The costs associated with this problem must be properly analysed, so that the promotion of safety is seen as an investment and not an expense.…”
Section: Safety In Paediatric Intensive Carementioning
confidence: 99%
“…In order to improve the safety of the care provided in this context, after understanding the causes mentioned above, it is necessary to identify the most effective solutions, with care bundles, checklists, double check systems, structured shift passages and point of care, rapid response systems and information and communication technologies being some of the resources suggested in the literature (27,(45)(46)(47)(48). In order to assess the impact, speci c quality indicators can be used to evaluate the outcomes, such as: mortality rate, rate of unplanned readmissions, the length of stay adjusted to the clinical severity and the rate of injuries, therapeutic errors, unscheduled extubations, incidents associated with vascular access, infections associated with healthcare and equipment-induced damage (1,21,49).…”
Section: Safety In Paediatric Intensive Carementioning
confidence: 99%